A Comparative Study of Sindbad-name and Bakhtiyar-name in term of Contributors Paatern of Narrative - Najme Hosseini Sarvari (متن شناسی ادب فارسی, 2019)
This study compares the stories of Sindbad-name and Bakhtiyar-name. The essential grounds for this comparison are the structural similarity between the scripts, as well as the fundamental differences in terms of actions’ modalities, actors’ roles, and the connections between them. The basis for this study is Greimas Theory and the communication model of characters, which assist the study to systematically identify the characters’ contributions in the events, and their motivations, demands and wills in the incidents and actions of the story. The results of this study show that Sindbad-name is the story of active characters and their wills and demands, while Bakhtiyar-name tells the story of fate and its indisputable dominance over the characters’ lives and their connections, in which women are more under the control of fate’s power and men’s role-playing and influence. Accepting the fact that literary scripts, especially folk tales with simple structures and sequence, are the reflections of the social environment of their particular historical era, it needs to be admitted that Bakhtiyar-name belongs to the era of believing in the undisputed power of fate and destiny; the era in which women are marginalized even more than before.